Subjective Responsibility in Socioeconomic Criminality - Corcoy Bidasolo, Mirentxu (2019)
The concept of willful intent is one of the most important discussions in Criminal Law. In this article, the author analyses the specific problems that arise regarding the proof of the subjective type in the ambit of socioeconomic criminality. To this end, the determination of the authorship of the crime is analyzed based on the criteria of competence and the willful intent that derives from it, as well as the question of the so-called willful blindness. The article aims to link theoretical and practical problems together, particularly, the proof in criminal proceedings. It is regarding this aspect that the modern jurisprudential conception of willful intent as a fact that must be proven through objective data acquires great relevance in this investigation.